Oligonucleotide therapy: An emerging focus area for drug delivery in chronic inflammatory respiratory diseases. (1st August 2019) - Mehta, Meenu; Deeksha,; Tewari, Devesh; Gupta, Gaurav; Awasthi, Rajendra; Singh, Harjeet; Pandey, Parijat; Chellappan, Dinesh Kumar; Wadhwa, Ridhima; Collet, Trudi; Hansbro, Philip M.; Kumar, S Rajesh; et al.
Abstract: Oligonucleotide-based therapies are advanced novel interventions used in the management of various respiratory diseases such as asthma and Chronic Obstructive Pulmonary Disease (COPD). These agents primarily act by gene silencing or RNA interference. Better methodologies and techniques are the need of the hour that can deliver these agents to tissues and cells in a target specific manner by which their maximum potential can be reached in the management of chronic inflammatory diseases. Nanoparticles play an important role in the target-specific delivery of drugs. In addition, oligonucleotides also are extensively used for gene transfer in the form of polymeric, liposomal and inorganic carrier materials. Therefore, the current review focuses on various novel dosage forms like nanoparticles, liposomes that can be used efficiently for the delivery of various oligonucleotides such as siRNA and miRNA. We also discuss the future perspectives and targets for oligonucleotides in the management of respiratory diseases. Highlights: Oligonucleotides are polynucleic acids consists of five base pairs. They act by altering gene expression of an affected individual. In respiratory diseases they are emerging as a newer therapy.